ADMIRAL ELPHINSTONE AND THE CONQUEST AND DEFENCE OF THE CAPE OF GOOD HOPE, 1795-96 - Potgieter, Thean; Grundlingh, Albert (Scientia Militaria - South African Journal of Military Studies, 2011)
Vice Admiral of the Blue the Honourable Sir George Keith Elphinstone (1746-1823) was appointed as commander of the British force dispatched to capture the Cape of Good Hope in 1795. As an experienced naval officer and a capable commander acquainted with the Cape and the Far East, he was the correct choice to command the expedition. Due to the strategic location of the Cape of Good Hope – literally halfway on the sea route to the East – it was vital for maritime communications, and Britain had to ensure that the Cape did not fall into French hands. To secure a safe base on the sea route to the East, a British expeditionary force was sent to the Cape. The British task force arrived in False Bay on 11 June 1795 and when negotiations with the Dutch authorities at the Cape failed, a military campaign commenced that resulted in the capitulation of the Cape on 16 September 1795. In August 1796, when a Dutch squadron under the command of Rear Admiral E. Lucas anchored in Saldanha Bay, Elphinstone speedily neutralised the threat, forcing Lucas to surrender. After a very successful service period at the Cape, Elphinstone returned to Britain on 7 October 1796. He conducted the defence of the Cape with vigour and actively sought out his enemy, confirming British control of the Cape and the virtual impossibility of taking back the Cape with force of arms.